Expansion in the presence of FGF-2 enhances the functional development of cartilaginous tissues engineered using infrapatellar fat pad derived MSCs - Kelly, Daniel; Buckley, Conor (My University, 2012)
MSCs from non-cartilaginous knee joint tissues such as the infrapatellar fat pad (IFP) and synovium possess significant chondrogenic potential and provide a readily available and clinically feasible source of chondroprogenitor cells. Fibroblast growth factor-2 (FGF-2) has been shown to be a potent mitotic stimulator during ex vivo expansion of MSCs, as well as regulating their subsequent differentiation potential. The objective of this study was to investigate the longer term effects of FGF-2 expansion on the functional development of cartilaginous tissues engineered using MSCs derived from the IFP. IFP MSCs were isolated and expanded to passage 2 in a standard media formulation with or without FGF-2 (5ng/ml) supplementation. Expanded cells were encapsulated in agarose hydrogels, maintained in chondrogenic media for 42 days and analysed to determine their mechanical properties and biochemical composition. Culture media, collected at each feed, was also analysed for biochemical constituents. MSCs expanded in the presence of FGF-2 proliferated more rapidly, with higher cell yields and lower population doubling times. FGF-2 expanded MSCs generated the most mechanically functional tissue. Matrix accumulation was dramatically higher after 21 days for FGF-2 expanded MSCs, but decreased between day 21 and 42. By day 42, FGF-2 expanded MSCs had still accumulated ~1.4 fold higher sGAG and ~1.7 fold higher collagen compared to control groups. The total amount of sGAG synthesised (retained in hydrogels and released into the media) was ~2.4 fold higher for FGF-2 expanded MSCs, with only ~25% of the total amount generated being retained within the constructs. Further studies are required to investigate whether IFP derived MSCs have a diminished capacity to synthesise other matrix components important in the aggregation, assembly and retention of proteoglycans. In conclusion, expanding MSCs in the presence of FGF-2 rapidly accelerates chondrogenesis in 3D agarose cultures resulting in superior mechanical functionality.
PUBLISHED
Keywords: Bioengineering; FGF-2; Low oxygen tension; MSC expansion; Next Generation Medical Devices